PELATIHAN PEMBUATAN ROLL ON ANTI HIPERTENSI PADA DOSEN DI FAKULTAS ILMU KESEHATAN UNIVERSITAS MERDEKA SURABAYA - Eka Deviany Widyawaty; Agung Putri HSN (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Hypertension is still a health problem because it is the silent killer disease. Based on the results of Riskesdas in 2018, it was stated that the prevalence of hypertension was 34.1%. ¬Hypertension mostly occurred in the 55-64 years age group, namely 55.2%. This service activity aims to improve the knowledge and skills of lecturers in handling hypertension in Midwifery Study Program, Faculty of Health, Merdeka Surabaya University. The method used in this training activity is the lecture method, discussion, demonstration and practice. Pre-test is carried out at the beginning before the delivery of the material, then the delivery of material and discussion. The materials provided during the training included the raw materials needed, the tools prepared, the manufacture of essential oils, packaging and ended with a post test.Based on the comparison between the average pre-test and post-test scores, it was found that there is an increase in the average value. In the pre-test the average value of cadres is 50.0 then after given training materials related to anti-hypertensive essential oil, the average score rose to 87.5. This shows that the level of knowledge of the Faculty of Health, Universitas Merdeka Surabaya lecturers increased after being given training.Keywords: Essential Oil, Allium Sativum, Lavender, Blood Pressure, Elderly